Determining and Measuring Factors Influencing Housing Affordability in Bandung with Case Study at Singgasana Pradana - Gabriella, Milka; Rahadi, Raden Aswin (Journal of Business and Management, 2020)
Abstract. The house is one of basic human needs for living besides food and clothing. But as the  population grows in Indonesia and the limited land available, house prices from year to year tend to increase. Rising house prices will have an impact on one’s housing affordability. In this study, the author aims to explore factors influence housing affordability and measure the effect of each factor. There are six main factors tested that affect housing affordability, including; the growth of sharing economy, environment, price, purchase intention, location and facilities. This research was conducted quantitatively. The data used in this study are primary data obtained from conditional surveys distributed by the author. The method used in this study is ordinal logistic regression. The findings ofthis study is that the predictor variable that has the most impact is the growth of sharing economy. The calculation result shows that a person had to increase his or her housing affordability level by 1,704 times because of the growth of sharing economy. In conclusion, ones’ housing affordability is  influenced by personal choices and then followed by external factors offered by housing developers or property developers. Keywords: Housing Affordability, Measuring and Determining Factors, Houses, Bandung City